2021
DOI: 10.1101/2021.10.23.21265415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographical inequalities in the evolution of the COVID-19 pandemic: An ecological study of inequalities in mortality in the first wave and the effects of the first national lockdown in England

Abstract: Objectives This is the first study to examine how geographical inequalities in COVID–19 mortality rates evolved in England, and whether the first national lockdown modified them. This analysis provides important lessons to inform public health planning to reduce inequalities in any future pandemics. Design Longitudinal ecological study Setting 307 Lower-tier local authorities in England Primary outcome measure Age-standardised COVID–19 mortality rates by local authority and decile of index of multiple depriva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Our findings align with the fundamental causes theory proposed by Clouston et al (2021) on stages of disease transmission and the generation of health inequalities 2 . However, our recent analyses of geographical inequalities in mortality found that whilst death rates were higher across the first wave in more deprived areas, the lock down did reduce them 22 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings align with the fundamental causes theory proposed by Clouston et al (2021) on stages of disease transmission and the generation of health inequalities 2 . However, our recent analyses of geographical inequalities in mortality found that whilst death rates were higher across the first wave in more deprived areas, the lock down did reduce them 22 .…”
Section: Discussionmentioning
confidence: 85%
“…Our findings align with the fundamental causes theory proposed by Clouston et al (2021) on stages of disease transmission and the generation of health inequalities 2 . However, our recent analyses of geographical inequalities in mortality found that whilst death rates were higher across the first wave in more deprived areas, the lock down did reduce them22 .Reduced viral load across the country is an important aim that benefits all inhabitants, through a reduction in selection pressure on the virus, and reduced demand on healthcare. Lockdowns are an effective means of achieving this aim quickly, however their potential harms need to be carefully weighed, and their timings carefully considered -and to reflect both local and national need.…”
mentioning
confidence: 99%
“…the 20% most deprived LAs compared to the rest of the country). We chose to focus on the bottom 20% because in previous work ( Welsh et al, 2021a ), we found that the 20% most deprived local authorities had the highest COVID-19 age-standardised mortality rates during the first wave and that these bottom two deciles had significantly higher death rates than the other eight deciles. The relationship between IMD and COVID-19 mortality rates was also not linear in the first wave (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Weekly counts of COVID-19 deaths (based on any mention of Coronavirus in the death certificate) for the study sample of LAs (n = 311) were obtained from the UK Office for National Statistics (ONS) by date of registration ( Timson, 2021 ) for the period 1 st January 2020 to 4 th July 2020, the date at which many service and hospitality establishments were allowed to re-open to the public ( Department for Business, 2020 ; Prime Minister's Office, 2020 ). Age-standardised weekly COVID-19 death counts were approximated using monthly age-standardised rates available from the ONS ( Office for National Statistics, 2021b ; Welsh et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation